UNPAB Lecturer Assessment and Performance Model based on Indonesia Science and Technology Index. (March 2019) - Isa Indrawan, Muhammad; Alamsyah, Bhakti; Fatmawati, Irma; Samrin,; Rusiadi,; Shindi Indira, Sri; Nita, Surya; Manshuruddin,; Siregar, Marahadi; Pramono, Cahyo; Wahyono, Teguh; Afrina Siregar, Nur; et al.
Abstract: This paper describes the assessment and ranking of the performance of the lectures of Universitas Pembangunan Panca Budi (UNPAB). The assessment system is based on guidelines that have been passed by the chancellor. The ranking is done to produce a position where the ability of each lecturer is based on the amount of scientific work produced by the lecturer. Data analysis techniques used descriptive analysis by using the support data of lecturers' performance in Science and Technology Index. The results of the assessment and ranking explain the value categories, such as lecturers with excellent, good, moderate, low and without performance. The impact of the assessment is that most or 100 UNPAB lecturers were rewarded leaving for Penang in 2017.